Autologus normovolemic and hypervolemic hemodilution during surgery using 6% dextran 70 and lactated ringer solution: impact on mean arterial pressure, heart rate, hemoglobin and hematocrite (A preliminary study) (Faculty of Medicine Universitas Indonesia, 2006)
Autologous normovolemic hemodilution (ANH) is one of the methods to conserve blood donor (homologous). The decrease in hemoglobin (Hb) due to bleeding in major surgery will be minimized and the hematocrite (Hct) will be adjusted accordingly by this method. However, due to its impractical clinical application, another simpler hemodilution method is used, i.e. hypervolemic hemodilution (HHD), using 6% dextran 70 and lactated Ringer solutions. The aim of this randomized comparative study was to investigate the impacts of both hemodilution methods (ANH and HHD) on mean arterial pressure (MAP), heart rate (HR), hemoglobin (Hb) and hematocrite (Hct) in anesthetized patients undergoing major surgery. Fourteen (14) women fulfilling the inclusion and exclusion criteria were divided into 2 groups. Seven (7) women received ANH and seven (7) women received HHD method. There were significant statistical differences (P<0.05) between ANH and HHD groups in MAP and Hct after 1 minute (86.3±9.1 vs. 99.1±6.4 on MAP) and (27.3±1.7 vs. 31.5±4.4 on Hct) and after 20 minutes (87.7±7.3 vs. 98.3±6.8 on MAP) and (27.4±1.7 vs. 3.6±4.8 on Hct) post-hemodilution respectively. There was no difference in HR and Hb. No statistical difference between the four parameters tested after 120 minutes post-hemodilution. It may be concluded that both methods worth to be used in clinical setting although further studies are required. (Med J Indones 2006; 15:246-50)